2020
DOI: 10.18203/issn.2454-2156.intjscirep20203548
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the availability of essential medicines and inventory control practice at university of Gondar comprehensive specialized hospital, Amhara regional state of Ethiopia: institutional based cross-sectional study design

Abstract: <p class="abstract"><strong>Background:</strong> Assessment of availability of essential medicines is a critical component of universal health coverage and important factor to address patients’ satisfaction and increase their health seeking behavior. Proper inventory management of essential drugs in the health facilities is critical in ensuring availability of essential drugs. The objectives of the study were to assess availability of essential medicines and inventory control practice in univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
3
2
Order By: Relevance
“…It may be because the findings of the latter study were based on the findings of many health facilities, whereas this study reported findings from two separate health facilities. In addition, the report in this study was higher than the report in Gondar [27]. A study conducted in Jimma reported 55.65%…”
Section: Plos Onecontrasting
confidence: 74%
See 2 more Smart Citations
“…It may be because the findings of the latter study were based on the findings of many health facilities, whereas this study reported findings from two separate health facilities. In addition, the report in this study was higher than the report in Gondar [27]. A study conducted in Jimma reported 55.65%…”
Section: Plos Onecontrasting
confidence: 74%
“…Furthermore, the average stockout period in Shegaw Motta general hospital during the last six months was slightly longer than what was found in the Gondar study. However, the average stockout period in Motta health center was shorter than that in the Gondar study [27]. Among the medicines in the Shegaw Motta general hospital, ferrous salt + folic acid 150 mg + 0.5mg had the longest stockout period, with 157 days.…”
Section: Plos Onementioning
confidence: 81%
See 1 more Smart Citation
“…This was comparable with the study conducted in Ethiopia; the result revealed that the overall average availability of essential medicine was 19 (79.17%) and average stock out of medicine in the survey period was 5 (20.83%). 17 However, the findings of the current study showed a lower overall availability of essential medicines when compared to a study conducted in Gondar town 23.67 (91%). 18 The observed difference is probably because the health centers manage a limited number of medicines and they have a management effort.…”
Section: Discussioncontrasting
confidence: 90%
“…Hence, to avoid service interruptions, the health facilities may purchase the required pharmaceuticals from private wholesales after receiving a letter attesting to the stock out of the products at the agency hubs [16]. Studies show that the majority of public health facilities in Ethiopia face a frequent shortage of medicines [17][18][19][20][21] and the percentage availability does not exceed 80% [22]. This is contrary to the aim of the Sustainable Development Goal (SDG), which promotes "access to safe, effective, high quality, and affordable essential medicines and vaccines for all" as a core element of Universal Health Coverage [23].…”
Section: Introductionmentioning
confidence: 99%